Effect of Irrigation Intervals on Evapotranspiration and Growth of Papaya - Ismail, Aeshah (1994)
Papaya a crop with potential for expansion IS sensitive to drought and waterlogging. Although in Malaysia irrigation is provided to supplement the uneven rainfall distribution, reliable data on crop evapotranspiration are required to design a proper irrigation system so as to apply the correct amount of water at the right time. An experiment was conducted to determine the actual evapotranspiration (ET) of papaya plant and the effect of irrigation intervals on crop growth. Papaya seedlings were transplanted into containers and observed for about 38 weeks under glass. They were irrigated through emitters at irrigation intervals of 1, 2, 4 and 8 days. ET varied between the four treatments. The daily-irrigated plants gave the highest ET, an average of 5.9 mm/day, and those with an 8-day interval, the lowest, an average of 3.1 mm/day. The plant height, number of leaves and girth measurements did not show a marked difference. However, flowering occurred only in plants subjected to daily and 2-day irrigation intervals and not in the other treatments.